FRI0627 Inadvertent yellow fever vaccination of patients with immune mediated inflammatory disease in private practice. (12th June 2018) - Fernandes, L.; Pippa, M.; Macedo, C.; Brudnewski, J.; Palacios, F.; Mahlmann, H.; Aliberti, L.; Kochen, J.; Aurichio, R.; Dourador, E.; Omura, F.; Hehn, F.; et al.
Abstract : Background: Yellow Fever (YF) is an endemic disease, in specific areas of Brazil. Since 1942, no new urban cycle cases have been observed. Yet, in early 2017, outbreaks of YF were reported in many states, outside the endemic areas, where YF was not considered a risk. Hence, new and some fatal cases have been reported including in highly populated areas close to the city of São Paulo. As it has been widely broadcasted, population searching for vaccination significantly increased and cases of inadvertent vaccination have been registered. Objectives: To analyze the consequences of inadvertent YF primo-vaccination in patients with immune mediated inflammatory diseases (IMID). Methods: Observational study (12/2017–01/2018).54 rheumatologists from private practice at different areas of São Paulo included specific YF information in their patients' orientations and actively searched for IMID patients that have received YF vaccination (YFV) inputting the data in a web-based questionnaire. Results: 56 patients received YFV; female 42 (75%), mean (±SD) age= 56±14 yr, median disease duration= 7 yr (6 months-45 yr), Diagnosis: RA (n=39; 72%), PsA (n=5), AS (n=4), 2 SLE, 3 vasculitis, 2 SS, one ReA and 2 UA. Treatment: 30 (54%) were considered under current strong immunosuppression (CE≥20 mg, MTX>20 mg, leflunomide, tofacitinib and biologic agents (BA); 18 (32%) were on biologic agents (9 anti-TNF, 2 abatacept, 3 tocilizumab, 1 rituximab, 1 patient each secukinumab and tofacitinib). Remaining patients were receiving csDMARDs isolated or in combination, with or without low CE (≤10 mg). Vaccination: 54 (96%) cases were primo YFV and 43 (80%) related inadvertent YFV. Adverse events (AE): 7 patients (13%) had AE after a median of 4 days (hours-60 days);3 of them were on BA, corresponding to 17% of the total subjects on various BA. Severity of AE:4 patients had mild AE (local pain, vertigo, fever, headache, myalgia), in 2 of them, symptoms promptly resolved while 2 needed medical assistance (one was on tocilizumab). Of the 3 remaining cases, one had severe reaction one hour after YFV (probably anaphylaxis); Finally, 2 patients had severe AE requiring hospitalization: one had meningitis (RTX+MTX) and other (ADA+MTX), abdominal pain, myalgia, fever, headache, vertigo and increased liver enzymes. No fatal events were observed. Concerning the vaccine effect on disease activity, only 5 (9%) patients related worsening of the disease after YFV, but 2 of them also presented AE. Conclusions: The small number of reports precludes any conclusion about rate/severity of AE and YFV in immunosuppressed rheumatic patients. Nevertheless, it emphasized the necessary awareness and careful analysis of the risk-benefice of YFV in this population. The interference of YFV on IMID disease activity seems to be marginal. On the other hand, this descriptive analysis clearly demonstrated persistence of patient's unfamiliarity with concepts of immunosuppression and its consequences, disclosing another unmet need in the management of patients with RD. Disclosure of Interest: None declared